2001
DOI: 10.1007/s00251-001-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mapping of the host resistance locus to rodent malaria (Plasmodium yoelii) infection in mice

Abstract: The disease outcome in malaria caused by the protozoan parasite Plasmodium is influenced by host genetic factors. To identify host genes conferring resistance to infection with the malaria parasite, we undertook chromosomal mapping using a whole-genome scanning approach in cross-bred mice. NC/Jic mice all died with high parasitemia within 8 days of infection with 1 x 10(5) parasitized erythrocytes. In contrast, 129/SvJ mice all completely excluded malaria parasites from the circulation and remained alive 21 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…This difference in susceptibility to malaria infection between mouse strains has prompted genetic studies in informative backcross and F2 progenies, as well as in recombinant inbred and congenic strains. These studies have confirmed that genetic susceptibility to malaria is indeed complex and have resulted in the mapping of several loci associated with susceptibility to P. chabaudi (Char1-8), [4][5][6][7][8][9] P. yoelii (Pmyr) 10 and P. berghei.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…This difference in susceptibility to malaria infection between mouse strains has prompted genetic studies in informative backcross and F2 progenies, as well as in recombinant inbred and congenic strains. These studies have confirmed that genetic susceptibility to malaria is indeed complex and have resulted in the mapping of several loci associated with susceptibility to P. chabaudi (Char1-8), [4][5][6][7][8][9] P. yoelii (Pmyr) 10 and P. berghei.…”
Section: Introductionmentioning
confidence: 64%
“…10 An over-representation of the WLA allele at this locus was observed among the mice that resisted early death (Table 3). In fact, only 5.3% of the mice that died early (before 13 days postinfection) were homozygous for the WLA allele, while 55% were C57BL/6 homozygous at the marker D1Mit221.…”
Section: Resultsmentioning
confidence: 99%
“…The peak LOD score was identified at 59.7 Mb (for marker rs9_6; NCBI ID: rs3685575). Char10 is proximal to the P. chabaudi resistance locus, Char1, which has been previously localized around position 100 Mb 36,37 ( Figure 6a). Subsequent analysis of chromosome 9 using additional mice from a fourth batch of F2 mice (n ¼ 237 total; males ¼ 140, females ¼ 97) and a subset of microsatellite markers, increased the LOD score to 10.8 and decreased the 95% credible interval to 17 Mb, from 51.3 to 68.3 Mb (Supplementary Figure 2).…”
Section: Iron Overload In Acb62 Tissuesmentioning
confidence: 99%
“…46,47 In an early study, it was shown that the BALB/c.D2 congenic mouse strain (congenic for the mtv-7 locus, located on the distal region of chromosome 1) exhibits an altered susceptibility phenotype to the parental BALB/c line, suggesting that this locus is involved in resistance to P .yoelii infection. 48 Ohno and colleagues 49 have reported the results of a genome-wide search for resistance QTL to P. yoelii infection. Their study was conducted in a BC resource population.…”
mentioning
confidence: 99%